Impact of rumen-protected glucose on performance, milk composition, and selected blood metabolites of early lactating Holstein Friesian cows - Yu, Hairui; Rahman, Abdur; Rahman, Hafeez Ur; Khan, Muhammad; Mushtaq, Maida; Quan, Guobo; Zafar, Muhammad Hammad; Li, Zijian; Rahman, Muhammad Aziz Ur (Frontiers in Veterinary Science, 2024)
IntroductionHigh-producing dairy cows often face calving stress and reduced feed intake during the transition period, leading to body fat mobilization to meet production demands. Supplementing rations with energy-dense sources like rumen-protected glucose (RPG) may enhance production performance in early lactation.MethodsThis study evaluated the effects of RPG supplementation on feed intake, body condition score (BCS), production performance, and blood metabolites in 32 early-lactation Holstein Friesian cows (6 ± 1 DIM; milk yield: 30 ± 5 kg/day; body weight: 550 ± 50 kg; BCS: 3.00 ± 0.25). Cows were assigned to four groups (n = 8/group) and fed a basal diet (Control) or supplemented with 150 g (S-150), 300 g (S-300), or 450 g (S-450) of RPG for a 42-day trial after 2 weeks of adaptation.ResultsResults showed significant improvements (p < 0.05) in final body weight, milk yield, energy-corrected milk, and milk-to-feed ratio with RPG supplementation, with the highest effects observed at 450 g/day. Milk components, including solids-not-fat, lactose, and total solids, also increased significantly. While feed intake remained similar (p > 0.05), blood glucose levels rose, and non-esterified fatty acids and β-hydroxybutyric acid concentrations decreased (p < 0.05), indicating reduced ketosis and negative energy balance.ConclusionThese findings suggest RPG supplementation at 450 g/day improves milk production, quality, and metabolic health in early lactating cows, warranting further exploration of higher dosages like 500–550 g/day.